Simultaneous Isolation of 6-Gingerol, 6-Shogaol, and 6-Paradol from Zingiber Officinale Using Vaccum Liquid Chromatography - Devi Permatasari; Anisyah Is Purwati; Prasetyawan Yunianto (JURNAL SAINS NATURAL, 2022)
Zingiber officinale (Ginger) was widely known as one of the most herbal medicines containing many bioactive compounds claimed to be useful as an antioxidant, anti-inflammatory, anti-cancer, and anti-coagulant. Gingerol, shogaol, and paradol are some of the most bioactive compounds found in ginger. Several studies have been conducted to isolate the bioactive compounds. However, a study about simultaneous isolation with a fast and effective methodology has yet to be found in Indonesia. Therefore, this study aimed to simultaneously isolate the bioactive compounds such as 6-gingerol, 6-shogaol, and 6-paradol in ginger using Vacuum Liquid Chromatography (VLC). Etil acetate (EA) fraction from the ginger crude extract was treated with VLC using a mix of hexane-EA as a mobile phase to gain the isolates, and then it was purified using HPLC semi-prep. 6-gingerol and 6-shogaol were found in the fraction of VLC 80% hexane. Meanwhile, 6-paradol was found in the fraction VLC 90% hexane. Further isolation of each compound was conducted using semi-prep HPLC. LC-MS was used to confirm the molecular weight of each isolate compared to the literature. This study obtained isolate 6-gingerol, 6-shogaol, and 6-paradol with a purity of 99%, 94%, and 92%, respectively.Keywords: Isolation; Zingiber officinale; 6-gingerol; 6-shogaol; 6-paradol; VLCABSTRAKIsolasi 6-Gingerol, 6-Shogaol, dan 6-Paradol dari Tanaman Zingiber officinale (Jahe) secara Simultan dengan Menggunakan Metode Vaccum Liquid Chromatography (VLC)Zingiber officinale (jahe) merupakan salah satu dari jenis tanaman obat yang memiliki banyak kandungan senyawa aktif yang bermanfaat sebagai antioksidan, antiinflamasi, antikanker, dan antikoagulan. Gingerol, shogaol, dan paradol adalah beberapa jenis senyawa aktif yang umumnya dapat ditemukan pada tanaman ini. Sejumlah penelitian telah dilakukan untuk proses isolasi senyawa tersebut. Akan tetapi, di Indonesia, isolasi senyawa tersebut belum dilakukan secara simultan dan efektif. Oleh karena itu, penelitian ini bertujuan untuk melakukan isolasi senyawa aktif 6-gingerol, 6-shogaol, dan 6-paradol secara simultan menggunakan metode Vaccum Liquid Chromatography (VLC). Fraksi etil asetat dari ekstrak jahe di VLC dengan campuran perlarut heksan-etil asetat (EA) untuk memperoleh isolat senyawa dan kemudian dimurnikan dengan menggunakan HPLC semi-prep. Pada hasil VLC 80 % heksana didapatkan senyawa 6-gingerol dan 6-shogaol. Sementara senyawa 6-paradol didapatkan pada VLC 90 % heksana. Selanjutnya, konfirmasi berat molekul senyawa dilakukan menggunakan LC-MS untuk mecocokkan dengan literatur yang sudah ada. Dari hasil penelitian didapatkan isolat senyawa aktif jahe berupa 6-gingerol, 6-shogaol, dan 6-paradol, masing-masing dengan kemurnian 99 %, 94 %, dan 92 %.Kata kunci : Isolasi, Zingiber officinale, 6-gingerol, 6-shogaol, 8-paradol, VLC